Mechanistic - Laurenczy, Gábor; Faure, Matthieu; Vieille-Petit, Ludovic; Süss-Fink, Georg; Ward, Thomas R (My University, 2002)
In situ high-pressure NMR spectroscopy of the hydrogenation of benzene to give cyclohexane, catalysed by the cluster cation [(eta(6)-C6H6) (eta(6)-C6Me6)(2)Ru-3(mu(3)-O)(mu(2)-OH)(mu(2)-H)(2)](+) 2, supports a mechanism involving a supramolecular host-guest complex of the substrate molecule in the hydrophobic pocket of the intact cluster molecule.
Keywords: benzene hydrogenation; biphasic conditions; high-pressure NMR; spectroscopy; supramolecular cluster catalysis; AQUEOUS-SOLUTION; COMPLEXES; EXCHANGE; ACTIVATION